Faktor Customer Review dan E-Service Quality terhadap Keputusan Pembelian Shopee - Tiffany, Milenia; Singagerda, Faurani Santi (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to examine the influence of Customer Review and E-Service Quality, on purchase decisions mediated by the level of customer trust of the Shopee Application Methodology/Approach: The testing method used in this study was a quantitative method. This study used a questionnaire to collect data. The questionnaire was distributed by random sampling through Google Forms. Hypothesis testing was performed using a Structural Equation Model (SEM). Results/Findings: The results showed that online customer reviews had no effect on shopee purchase decisions, e-service quality had an effect on shopee purchase decisions, trust had an effect on shopee purchase decisions, trust weakened the influence of customer reviews on purchase decisions and trust weakened the influence of customer reviews on decisions purchase.Conclusions: Online customer review tidak berpengaruh terhadap keputusan pembelian di Shopee, sedangkan e-service quality dan trust memiliki pengaruh signifikan terhadap keputusan pembelian. Selain itu, trust memperlemah pengaruh customer review terhadap keputusan pembelian, sehingga Shopee perlu meningkatkan kualitas pelayanan inti untuk menjaga kepercayaan pelanggan.Limitations: This research is only limited to the variables of online customer reviews, e-service quality trust, and purchase decisions. There are many other factors that are very likely to be raised and explored for future research.nContribution: This research is expected to improve the purchase decisions and serve as a reference for further research.